Highly expressed odorant receptor orthologs detect the aggregation pheromone lineatin in Trypodendron ambrosia beetles - Andersson, Martin N; Biswas, Twinkle ; 0000-0001-6106-0611; Yuvaraj, Jothi Kumar (Molecular Ecology, 2025)
Chemical communication using pheromones is crucial for the reproductive success of many insect species, including beetles (Coleoptera). Pheromones are detected by specialised odorant receptors (ORs), called pheromone receptors (PRs), in the sensory neurons of the antennae. The PRs in Coleoptera remain understudied, with only a few receptors being functionally characterised. This limits our understanding of their response specificities and evolutionary origins. To this end, we aimed to identify PRs in two species of ambrosia beetles (Curculionidae; Scolytinae), the conifer-attacking Trypodendron lineatum (‘Tlin’) and the congener T. domesticum (‘Tdom’), specialising in deciduous trees. Both species use the female-produced aggregation pheromone lineatin for host-and mate finding. To date, no OR has been functionally characterised in ambrosia beetles. We specifically aimed to investigate the response specificity of the candidate PRs and their evolutionary relationships with PRs in other curculionids. We annotated 53 ORs from a T. domesticum antennal transcriptome, whereas ORs from T. lineatum were reported previously. We reveal numerous conserved Trypodendron OR orthologs with high sequence identity, with one orthologous pair (TdomOR13/ TlinOR13) having much higher expression than all other OR genes. Through functional characterisation in HEK293 cells, we show that these receptors respond exclusively to lineatin. We further show that the receptors are phylogenetically well separated from all other known beetle PRs, including those in other curculionid species. This is the first study to demonstrate functional conservation of PR orthologs in congeneric beetles, and our findings support a scenario in which coleopteran PRs have evolved on multiple independent occasions.